Seroprevalence of Human, Sheep and Goat brucellosis in Raparin District (Raparin Journal of Humanities (RJH), 2019)
Brucellosis is a worldwide disease caused by an infectious bacterial disease called Brucella, it has some species in genera. Prevalence of the brucellosis in many area of the world particularly in some Mediterranean and Middle East countries. A total 494 sera samples were collected from 36 herds in Raparin district including 113 human sera (herder), 199 sheep and 182 goat sera sample.Using three serological such as Rosbengal test (RBT), 2-Mercaptoethanol test (2ME) and Enzyme linked immune sorbent Assay (ELISA) detect the prevalence of brucellosis in the district according to animal species, gender, vet office area and age group with a comparison between serological tests which was used in this study during august 2017 till jun 2018 . All samples collected from adults of both sexes from different seven geographical areas in Raparin district. The total prevalence of brucellosis was 26.3% this value varied according to ifferent areas. The highest in Sangasar and Bngrd was 37.3%, and 35.3% while the lowest in Rnia and Zharawa was 13.2%, and 16.9% respectively, using the Rose-bengal test as a screening test to identify the prevalence of the disease. The total prevalence was varied according to the animal species, gender and age group. The study revealed that the prevalence of the disease varied according to the used type of the serological tests. RBT recorded the highest 26.3% then the 2-Mercapto-ethanol test recorded (14.4%) and ELISA recorded (12.4%), When comparing the positive results of ELISA and other serological tests the results reveals significant (P